О сравнительном анализе дифференцирующих звеньев с эмиттерными повторителями - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
Two schemes of differentiating links are analyzed. The advantages of a link with the supply of an input signal through a capacitor to the base-emitter junction of a transistor for differentiation are shown.